2017
DOI: 10.1136/emermed-2016-206115
|View full text |Cite
|
Sign up to set email alerts
|

Can the prehospital National Early Warning Score identify patients most at risk from subsequent deterioration?

Abstract: Our findings suggest that the NEWS could successfully be used by ambulance services to identify patients most at risk from subsequent deterioration. The implementation of this early warning system has the potential to support ambulance clinician decision making, providing an additional tool to identify and appropriately escalate care for acutely unwell patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 16 publications
2
53
0
1
Order By: Relevance
“…Also, by including only patients evaluated and evacuated in ALS, a high number of older adults were involved. This fact nonetheless reflects the target population of our geographic area, and it is in line with similar studies [9]. On the other hand, because data extraction was done on a nonblinded procedure, the cases were only considered if the mortality occurred-due to any cause-within the hospital and within the first 48 h after EMS care, in order to minimize the selection bias.…”
Section: Strength and Limitationsmentioning
confidence: 63%
See 2 more Smart Citations
“…Also, by including only patients evaluated and evacuated in ALS, a high number of older adults were involved. This fact nonetheless reflects the target population of our geographic area, and it is in line with similar studies [9]. On the other hand, because data extraction was done on a nonblinded procedure, the cases were only considered if the mortality occurred-due to any cause-within the hospital and within the first 48 h after EMS care, in order to minimize the selection bias.…”
Section: Strength and Limitationsmentioning
confidence: 63%
“…Our study shows that by incorporating a subsequent assessment of the pLA, a better characterization of the risk of mortality in patients with low risk is achieved. In this way, care professionals may know in advance the severity of the condition they are confronting and the actual need for evacuation, which certainly may facilitate the decision-making process [9,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that emergency medical services (EMS) are able to identify and track critically ill, high‐risk patients. Previous studies have demonstrated very encouraging results in the prehospital performance of NEWS in predicting mortality and likelihood of ICU admission and it has been suggested to be included in prehospital systems . A recent review noted a low number of studies assessing the use of early warning scores in a prehospital setting and their results were inconclusive and thus a further study was deemed justifiable.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, 98% of hospitals use track and trigger systems (National Confidential Enquiry into Patient Outcome and Death (NCEPOD) 2012). The use of NEWS is supported by evidence of its sensitivity in accurately predicting deterioration in patients who are acutely ill (Smith et al 2013, Bilben et al 2016, Shaw et al 2017. Despite this welldefined and widely used system, there is evidence that nurses do not consistently follow guidelines and trigger appropriate responses when presented with deteriorating patients (Donaldson et al 2014).…”
Section: Nicholas Woolfe Loftus and Duncan Smithmentioning
confidence: 99%